Risk Factor distribution in patients with Acute Coronary Syndrome - KC, Man Bahadur (Nepalese Heart Journal, 2003)
Coronary Artery disease is emerging as a growing epidemic in whole of the South Asia region. South Asians are genatically most predisposed people to Coronary Artery disease. In this background of genetic predisposition to Coronary Artery disease and changes in life style, which increases the vulnerability to acquire this disease, many Nepalese people are getting Coronary Artery disease with increasing number every year.